Unveiling the regulatory mechanisms behind SUMOylation to improve rice abiotic stress response - Rosa, Margarida T. Gomes (2022)
"Climate change is one of the biggest concerns worldwide due to its effect on many physical and biological systems. Intense episodes of drought, heat, cold, and high salinity are becoming more frequent, compromising crop productivity. Thus, it is crucial to equip the plants with tools that will allow them to grow in such erratic/sub-optimal climate conditions. In order to achieve these biotechnological improvements, it is of utmost importance to understand the molecular mechanisms governing stress tolerance in crops, such as rice.(...)"